In situ Pulmonary Artery Thrombosis: A Previously Overlooked Disease - Cao, Yunshan; Geng, Chao; Li, Yahong; Zhang, Yan (Frontiers in Pharmacology, 2021)
Pulmonary thromboembolism (PTE) is the third leading cause of death in cardiovascular diseases. PTE is believed to be caused by thrombi detached from deep veins of lower extremities. The thrombi travel with systemic circulation to the lung and block pulmonary arteries, leading to sudden disruption of hemodynamics and blood gas exchange. However, this concept has recently been challenged by accumulating evidence demonstrating that de novo thrombosis may be formed in pulmonary arteries without deep venous thrombosis. On the other hand, chronic thromboembolic pulmonary hypertension (CTEPH), a subtype of pulmonary hypertension, could have different pathogenesis than traditional PTE. Therefore, this article summarized and compared the risk factors, the common and specific pathogenic mechanisms underlying PTE, in situ pulmonary artery thrombosis, and CTEPH at molecular and cellular levels, and suggested the therapeutic strategies to these diseases, aiming to facilitate understanding of pathogenesis, differential diagnosis, and precision therapeutics of the three pulmonary artery thrombotic diseases.